Fat Intake, Blood Pressure and Randomed Blood Glucose Levels as Risk Factor of Metabolic Syndrome in Adolescent of Junior School in Denpasar City - Suiraoka, I Putu; Moviana, Yenny; Cintary, Lely (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
The metabolic syndrome in children is defined when 3 of the 5 components are classified: hypertension, low HDL cholesterol, high serum triglyceride, high blood glucose levels, and central obesity. This study was a retrospective study with case-control design. Data collection was conducted from August to October 2014. The population of this study were all students in 8 selected junior high schools. Based on the calculation result, it was known that the sample size for case and control group are 128 people. Case and control determination began with screening of waist circumference using a tape measure, measured from the diameter between the lower ribs 10 with the iliac crest at the end of normal expiration. Systolic and diastolic blood pressure was measured using a digital blood pressure gauge under the Omron brand. Blood glucose levels were measured using a multicheck parameter tool under the Nesco brand. BMI based on weight and height were measured using body scales and Microtoise. Fat intake data were collected using semi-quantitative food frequency method. Data were analyzed descriptively in the range and mean for waist circumference variable, blood pressure, randomed blood glucose levels, and fat intake. Furthermore, the calculation of Odd Ratio. Based on the results be concluded that adolescents who consume fat above 25% risk 3.3 times greater to experience metabolic syndrome. Systolic and diastolic blood pressure, BMI and blood glucose levels as the case group was higher than the control group.